STRATEGI PENGEMBANGAN KREATIVITAS DALAM MENGUASAI TEKNOLOGI YANG TERINTEGRASI DI MAN 1 KOTA TANGERANG BANTEN - Munawati, Siti; Hasim, Hasim; Rosbandi, Rosbandi (Universitas Islam Syekh-Yusuf, 2024)
Technological developments that continue to develop require that students at MAN 1 Tangerang City, which is marked by technological developments, need to develop creativity that is in line with the times, such as an orientation towards technological progress itself with various learning applications that support them to be skilled and able to balance the use of technology in Integration is still at the implementation and adaptive level, this is to increase creative abilities. Creativity does not immediately appear in students, but a stimulus needs to be given to build creativity. Efforts to build creativity can start by giving freedom of expression, providing creative tools, inviting students to carry out activities together, motivating students to give them a lot of time and managing it, inviting them to study technology with various multimedia that supports learning and respecting and appreciating ideas. they. Media that is considered capable of helping improve student learning outcomes is media that can combine elements of images, text, animation from PowerPoint, multimedia presentations, video editors, email, WAG discussions, Canva and many other technological media. So this school can be built by creating education that is creativity-oriented, multidisciplinary curriculum, problem-based learning, design thinking, and freedom of expression with technology. The author's research method is qualitative methodology, which is a particular tradition in social knowledge that fundamentally depends on human observation. Next, in collecting data the author applied three steps, namely direct inspection of the field (observation), then interviews, and finally documentation. The data analysis carried out consisted of several stages, namely data reduction, then data presentation, and drawing conclusions.